Kesenjangan Literasi dan Akses Pendidikan sebagai Tantangan Penyuluhan HAM bagi Anak Binaan dalam Kerangka Perlindungan Hukum di LPKA Bandung - Zorya Kanoubie Attar Bakhri; Yoyoh Anggreni; Fathir Putra Maulud; Gia Anggiani; Ahmad Ramdani (Yayasan Al-Afif, 2025)
This study examines the effectiveness of Human Rights (HAM) education for ten juvenile inmates aged 15–20 at the Lembaga Pembinaan Khusus Anak (LPKA) Bandung, focusing on three core aspects: the children’s literacy levels and educational backgrounds, challenges encountered during the educational sessions, and the alignment of these practices with legal standards of child protection. The research employs an empirical juridical method combined with normative analysis based on Indonesian legislation and international human rights instruments. Findings reveal that low literacy levels and irregular educational histories significantly hinder the juveniles’ comprehension of fundamental human rights concepts. Several challenges emerged during implementation, including limited legal vocabulary, difficulties sustaining attention, psychological barriers, and inadequate learning facilities. From a legal perspective, the program aligns with major child protection principles under the Child Protection Act, the Juvenile Criminal Justice System Act, the Convention on the Rights of the Child, and the Havana Rules, although the structural fulfillment of the right to education and information remains insufficient. This study highlights the need for more adaptive educational methods and underscores the state’s responsibility to ensure accessible, high-quality education for children in custodial settings.